¿El sistema de eliminación de barreras burocráticas es constitucional?: Un debate a partir del caso de la tercerización laboral - Quiñonez López, Sonia (2024)
The present article discusses the constitutionality of the system for eliminating bureaucratic barriers implemented by the Comisión de Eliminación de Barreras Burocráticas (CEB) and the Sala de Eliminación de Barreras Burocráticas (SEL) of INDECOPI. It demonstrates that these entities do not engage in strict constitutional review but are limited to declaring the illegality or unreasonableness of bureaucratic barriers without repealing the underlying norms. Thus, they do not assume jurisdictional functions nor conduct a proper constitutional review of general administrative provisions and administrative acts. Instead, they ensure the legality and reasonableness of administrative regulation, coexisting with other forms of constitutional control such as the popular action and diffuse control.